A ANALYSIS OF HEADWEAR AND BERET IN FASHION - Хожиев, Абдурахим (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Purpose: the purpose of the research is to improve the quality of the beret based on the analysis of women's headdresses, to make effective use of natural and seasonal fabrics. Methods: in this article, the history of creation and development of European, American and Asian headdresses, as well as the changes and losses that occurred during this interval, were studied. Various types of headwear were studied, and their fabrics were tested and analyzed for their physical and mechanical properties. The design-project construction documents for the production of women's headwear from the optimal options of gauzes with high air and water permeability characteristics of knitwear, cloaks, artificial leather, seasonal fabrics are proposed. Results: Weather conditions in the territory of Uzbekistan were analyzed and hair, scalp, skin diseases and symptoms caused by adverse weather were studied by medicine, taking into account hot and cold temperatures and negative health effects for women. It is planned to launch the production of comfortable and seasonal headgear that does not show secrets. Conclusion: it is applied to the production of beret in a new design using knitwear, plaid, artificial leather, natural and seasonal fabrics.